2019
DOI: 10.1038/s41598-019-48075-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silver oxidation on the photocatalytic activity of Ag/ZnO hybrid plasmonic/metal-oxide nanostructures under visible light and in the dark

Abstract: A new synergetic hybrid Ag/ZnO nanostructure was fabricated which is able to cause photocatalytic degradation (in high yields) of methylene blue under visible light as well as in the dark. In this nanostructure, ZnO was synthesized using the arc discharge method in water and was coupled with Ag via a chemical reduction method. X-ray photoelectron spectroscopy (XPS) and photoluminescence spectroscopy results confirmed the existence of defects in ZnO in the hybrid nanostructures; these defects act as electron tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 70 publications
4
47
0
Order By: Relevance
“…Dawoud et al 24 observed that Ag doped ZrO 2 nanoparticles are effectively degraded the RB dye in visible light irradiation because of the surface area, band gap and porosity. Similar degradation effect has been observed by Ziashahbi et al 25 using Ag decorated ZnO hybrid nanostructures against methylene blue under visible light.…”
Section: Introductionsupporting
confidence: 85%
“…Dawoud et al 24 observed that Ag doped ZrO 2 nanoparticles are effectively degraded the RB dye in visible light irradiation because of the surface area, band gap and porosity. Similar degradation effect has been observed by Ziashahbi et al 25 using Ag decorated ZnO hybrid nanostructures against methylene blue under visible light.…”
Section: Introductionsupporting
confidence: 85%
“…Therefore, PtNPs induce a blue shift in the optical spectrum of Pt/ZnO nanocomposites [126]. In this respect, plasmonic AgNPs are commonly employed to enhance photocatalytic efficiency of ZnO under visible light [127,128]. As mentioned, a Schottky barrier is established at the metal/ZnO interface when noble metal comes in contact with ZnO.…”
Section: Noble Metal Doped Znomentioning
confidence: 99%
“…Metal oxide semiconductor (MOS) based heterojunction nanostructures have been extensively used for a wide range of fascinating applications in the emerging fields of oxidation catalysis, 1 photocatalytic degradation, 2 CO oxidation, 3 photoelectrochemial water splitting, 4 toxic gas detection 5 etc. Among various heterojunction materials, MOSs with plasmon mediated interfacial catalytic properties due to surface anchored noble metal nanoclusters have shown excellent sensing properties, especially towards detection of oxidizing gases, like NO2.…”
Section: Introductionmentioning
confidence: 99%